Spinal cord stimulation for the treatment of complex regional pain syndrome: A systematic review of randomized controlled trials - Mattie, Ryan; Lin, Alan Bingtao; Bhandal, Harjot; Gill, Benjamin; Tram, Jennifer; Braun, Samamtha; Prabakar, Nitin; Yin, Claire Tian; Brar, Nick; Fox, Andrew; Saltychev, Mikhail (Elsevier, 2025)
Background
Spinal Cord Stimulation (SCS) is a widely recognized treatment for Complex Regional Pain Syndrome (CRPS), particularly in cases where traditional methods are ineffective. This paper systematically reviews randomized controlled trials to analyze the efficacy of SCS, as well as Dorsal Root Ganglion (DRG) Stimulation in treating CRPS, focusing on its long-term effectiveness.
Methods
This systematic review focused exclusively on randomized controlled trials to assess a primary outcome of improvement in pain symptoms in patients diagnosed with CRPS. The primary outcomes assessed were pain reduction and patient satisfaction, with attention to functional improvement, quality of life improvement, preference for waveform settings, and complications when such data was made available.
Results
The results showed significant pain reduction in CRPS patients treated with SCS and DRG. Preference for specific SCS settings varied among patients, with no clear superiority of one setting over another. Innovations in SCS technology, including novel waveforms and frequencies, demonstrated potential for enhanced efficacy and patient comfort.
Conclusions
The review underscores the importance of SCS and DRG as significant treatment options to reduce pain for patients suffering from CRPS. It highlights the need for ongoing research to optimize SCS therapy, focusing on individual patient preferences and responses to different stimulation parameters. This personalized approach could lead to improved patient outcomes in CRPS management. Additionally, as this study only contained data from Randomized Controlled Trials, inclusion of well-conducted observational studies may help to provide stronger evidence for use of this therapy in CRPS patients.